(untitled) - Soderberg, Richard W. (Boca Raton, 1994)
Flowing Water Fish Culture provides an in-depth discussion of the husbandry of fin fish in a stream of water. It guides the reader through the technical considerations of intensive aquaculture, including fish growth rates, hydraulic characteristics of fish rearing units, oxygen consumption rates in relation to oxygen solubility and fish tolerance of hypoxia, and water reconditioning by reaeration and ammonia filtration. Unlike other publications that provide only general overviews on the subject, this text/reference offers specific details that will be useful in the actual design and operation of a facility. Problem sets at the end of each chapter provide ample opportunity to develop skills. The information in the book is valuable for those teaching, considering, or practicing aquaculture at intensity levels ranging from conventional single-pass trout hatcheries to closed aquaculture systems.
Keywords: Fish culture; Water supply